Method development and validation of a new RP-UFLC method for the simultaneous estimation of Sofosbuvir and Velpatasvir in tablet dosage form using an internal standard - Priyanka Vallabh Deulkar; Mukthinuthalapati Mathrusri Annapurna (The Bioscan, 2025)
Sofosbuvir is an anti-viral drug used for the treatment of chronic hepatitis C virus infection and Velpatasvir is also an anti-viral drug used for the inhibition of hepatitis C virus and both the drugs acts directly. The combination of Velpatasvir and Sofosbuvir works by stopping the hepatitis C genotype 1, 2, 3, 4, 5, or 6 infection. A new RP-UFLC method has been proposed for the simultaneous estimation of Sofosbuvir and Velpatasvir in tablet dosage forms in presence of an internal standard. Shimadzu Model CBM-20A/20 Alite UFLC system with PDA detector and Zorbox Eclipse Plus C18 column was used for the chromatographic study. Mobile phase mixture consisting of 0.1 % Tri fluoro acetic acid: Acetonitrile (45: 55, v/v) with a flow rate 0.8 ml/min was chosen for the simultaneous determination of Sofosbuvir and Velpatasvir and the method was validated as per ICH guidelines. KEYWORDS Sofosbuvir, Velpatasvir, RP-UFLC, validation, ICH guidelines.